Cyber Violence in the Educational Environment - Dončev, Aleksandar; Jereb, Eva (Sodobni pristopi v kadrovskem managementu in izobraževanju, 2026)
The chapter deals with the issue of cyber violence in the educational environment. It emphasises the need for responsible use of digital media, which is key to safe and responsible use of digital technologies in schools. It demonstrates a systematic approach to digital inclusion education that encompasses a broader social and critical perspective on the use of digital media. The increased use of the Internet in schools brings opportunities but also challenges, such as cyberbullying, harassment, and stalking, the spread of fake news, the dangers of personal data misuse and identity theft, and addiction to digital devices. It is essential to understand how the anonymity and accessibility of digital platforms enable abuses that can have a profoundly negative impact on social and emotional well-being. The need for adequate infrastructure, cyber inclusion, and equal opportunities for all is highlighted.